Political connections and investment in rural Vietnam - Thomas Markussen; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper uses household panel data from rural Vietnam to explore the effects of having a relative in a position of political or bureaucratic power on farmers' agricultural investment decisions. Our main result is that households significantly increase their investment in land improvement as a result of relatives moving into public office. Connections to office holders appear to be important for investment because they strengthen de facto land property rights and improve access to off-farm employment and to informal loans. The findings underline the importance of informal networks for economic behaviour in environments with developing institutions and markets. They also suggest the presence of an untapped potential for economic development: if households without connections could obtain equally strong property rights and access to credit and insurance as the well-connected households, investment levels would rise substantially.
Keywords: D73; H7; O12; Q15; 330; political connections; informal networks; land property rights; investment; credit; Vietnam